A SIGNIFICANT CONTRIBUTION TO THE STUDIES OF BOOK PUBLISHING IN LATVIA - LIMANE, LILIJA (Knygotyra, 2015)
Department of Rare Books and Manuscripts the National Library of Latvia Jēkaba iela 6/8, LV-1050 Riga, Latvia E-mail: lilijal@lnb.lv